Overexpression of Interleukin-17 Modulates Responses to Marek’s Disease Virus Infection and Tumor Formation in Chickens - Nitish Boodhoo; Katherine Blake; Fatemeh Fazel; Janan Shoja Doost; Shayan Sharif (Viruses)
Marek’s Disease Virus (MDV) is a highly contagious pathogen in chickens, resulting in immunosuppression and T-cell lymphomas. Understanding the role of host cytokines in MDV pathogenesis is crucial for developing effective interventions. This study investigated the in vivo effects of overexpressing avian interleukin-17 (IL-17) in Marek’s disease virus infection model and its impact on T-cell populations. We utilized a recombinant pCDNA3.1 plasmid that expresses IL-17 at days 4 and 10 post-MDV infection in chickens. Our findings demonstrate that IL-17 overexpression significantly enhanced MDV replication. However, treatment with the plasmid expressing IL-17 led to a reduction in MD disease severity. Additionally, IL-17 treatment markedly altered the frequency of CD4+ and CD8α+ αβ T-cells. Specifically, at 21-dpi, there was an increase in CD3+ CD8α+ αβ T cells and a decrease in CD3+ CD4+ αβ T-cells within the spleen of chickens treated with the plasmid expressing IL-17. These modulatory effects suggest a possible mechanism by which IL-17 facilitates immune system cell activation and enhances viral persistence. This study underscores the pivotal role of IL-17 in MDV infection dynamics and offers.